A Global and Seasonal Perspective of Martian Water Vapor From ExoMars/NOMAD. Issue 11 (10th November 2021) - Crismani, M. M. J.; Villanueva, G. L.; Liuzzi, G.; Smith, M. D.; Knutsen, E. W.; Daerden, F.; Neary, L.; Mumma, M. J.; Aoki, S.; Trompet, L.; Thomas, I. R.; Ristic, B.; et al.
Abstract: Slightly less than a Martian Year of nominal science (March 2018–January 2020) with the ExoMars Trace Gas Orbiter has furthered the ongoing investigation of dayside water vapor column abundance. These dayside observations span latitudes between 75°S and 75°N, and all longitudes, which can provide global snapshots of the total water column abundances. In addition to tracking the seasonal transport of water vapor between poles, geographic enhancements are noted, particularly in the southern hemisphere, both in Hellas Basin, and in other regions not obviously correlated to topography. We report consistent water vapor climatology with previous spacecraft observations, however, note a difference in total water vapor content is noted. Finally, we are unable to find evidence for substantial diurnal variation in the total dayside water vapor column. Plain Language Summary: This work provides the first look at the ExoMars Trace Gas Orbiter's ability to track atmospheric water vapor on the day side of Mars, through downward looking observations. Water vapor is reported in a series of maps, with respect to geography and season, and find consistent water vapor climatology with precious spacecraft observations. These maps inform our understanding of where Martian water vapor moves throughout the year and where it is concentrated. Key Points: Water vapor can be retrieved robustly from the Nadir and Occultation for MArs Discovery limb and Nadir observatory nadir observations for most dayside conditions Retrieved water vapor columns demonstrate volatile transport, geographic variations, and lack of evidence for daytime local variations Trace Gas Orbiter observations continue the legacy of monitoring the Martian water cycle and will contribute to future modeling efforts